2012
DOI: 10.1111/j.1464-410x.2012.11343.x
|View full text |Cite
|
Sign up to set email alerts
|

Dutasteride, who is it more effective for? Second to fourth digit ratio and the relationship with prostate volume reduction by dutasteride treatment

Abstract: E 8 5 7What ' s known on the subject? and What does the study add? The second to fourth digit ratio (hereafter the digit ratio) of the right hand is related to the activity of the androgen receptor. Five α -reductase inhibitor (5ARI) reduces the prostate volume of patients with BPH. In terms of prostate volume reduction, large-scale placebo-controlled studies show that patients with BPH do not always respond well to 5ARI treatment.Patients with a higher digit ratio respond well to dutasteride treatment compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
7
1
Order By: Relevance
“…In addition, the mean value of the females’ digit ratio was lower than that of males in our previous studies (0.952,19 0.97,20 0.951,58 and 0.94859. However, in one study conducted among 664 (332 males, 332 females) university students (mean age: male: 22.4 years, female: 21 years), the digit ratio in Korean men was significantly lower than that of Korean women (0.96 vs 0.97, P < 0.001) 60.…”
Section: Discussioncontrasting
confidence: 56%
“…In addition, the mean value of the females’ digit ratio was lower than that of males in our previous studies (0.952,19 0.97,20 0.951,58 and 0.94859. However, in one study conducted among 664 (332 males, 332 females) university students (mean age: male: 22.4 years, female: 21 years), the digit ratio in Korean men was significantly lower than that of Korean women (0.96 vs 0.97, P < 0.001) 60.…”
Section: Discussioncontrasting
confidence: 56%
“…() showed a greater reduction in prostate volume after dutasteride treatment in higher digit ratio (≥0.95) group compared with lower digit ratio (<0.95) group (−24.5% vs. −17.5%, p = 0.027). This means that patients with higher digit ratios respond well to dutasteride treatment (Kim et al ., ).…”
Section: Discussionmentioning
confidence: 92%
“…A previous study reported that digit ratio is negatively correlated with fetal testosterone to fetal estradiol ratio (Lutchmaya et al ., ), that is, a high fetal testosterone to fetal estradiol ratio results in a low digit ratio. Zheng & Cohn () reported that digit ratio is controlled by the balance between androgen and estrogen signaling during digit development (Manning, ; Zheng & Cohn, ), and recently, it was reported digit ratio is related to BPH and BPH treatment (Kim et al ., ; Sudhakar et al ., ). Sudhakar et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations